Material Development for English Tourism Subject Based on the Local Wisdom - Safitri, Lia (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL; Vol 2 No 2 (2020): Education and Linguistics Knowledge Journal (Edulink), 2020)
This article aimed to review the development of English Tourism subject by involving local wisdom. This article discusses about the definition of material development, the principles in material development and need analysis for material development. It also defined local wisdom as one the points in material development. The next discussion explains about the procedures of material development and discusses material development for English Tourism subject based on the local wisdom. Based on the review, this article also gives recommendations how to involve local wisdom in material development and how to develop meaningful material for English Tourism subject.   Keywords : material development, local wisdom, English for Tourism